2018
DOI: 10.1177/0300060518807604
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aortic arch type on technical indicators in patients undergoing carotid artery stenting

Abstract: Objective This study was performed to explore the effect of the aortic arch type on technical indicators in patients undergoing carotid artery stenting (CAS). Methods The data of 224 consecutive patients who underwent unilateral CAS from January 2011 to December 2012 were retrospectively analyzed. The requirement for placement of the guiding catheter into the common carotid artery with assistance of an angiographic catheter, fluoroscopy time, contrast agent dose, and adverse events were recorded. Results The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…To appropriately determine the viability of left TAx TAVR, preprocedural CT assessment of the aortic arch should be used to confirm the angulation and position of the takeoff of the left subclavian artery from the aortic arch. 24,25) In type I aortic arch where the origin of all three major arteries are located in the same horizontal plane as the greater curvature of the aortic arch, the stiff wire and the delivery catheter can be efficiently advanced along the greater curvature of the ascending aorta. In this respect, the left TAx access should be selected preferentially since it closely mimics TF access.…”
Section: Discussionmentioning
confidence: 99%
“…To appropriately determine the viability of left TAx TAVR, preprocedural CT assessment of the aortic arch should be used to confirm the angulation and position of the takeoff of the left subclavian artery from the aortic arch. 24,25) In type I aortic arch where the origin of all three major arteries are located in the same horizontal plane as the greater curvature of the aortic arch, the stiff wire and the delivery catheter can be efficiently advanced along the greater curvature of the ascending aorta. In this respect, the left TAx access should be selected preferentially since it closely mimics TF access.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the TRA learning curve was overcome after performing 30 cases, which was the same as for TFA, because the operator was relatively experienced in TRA. Shen et al also found that TFA might be time-consuming in patients with type III and bovine aortic arch [25]. In the present study, for both TFA and TRA, the operator became skilled after performing 30 angiograms.…”
Section: E921631-7mentioning
confidence: 48%
“…We conducted a systematic literature review without meta-analysis per Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [8]. Nineteen studies were identified that discussed perioperative risk in the context of relevant anatomy [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (Table 1) in addition to fourteen studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41] (Table 2) and fifteen case reports/series [42][43][44][45][46][47][48][49][50][51][52][53][54]…”
Section: Resultsmentioning
confidence: 99%